Anterior Bowing of Tibia in an Adult: A Case Report (Global Journal of Medical Research, 2020)
A 35-year-old female presented to us with anterior bowing of her right tibia. The deformity developed in her adolescence and subsequently had not progressed for nearly two decades. The patient had no functional limitation, her only concern being cosmesis. Radiological investigations suggested either fibrous dysplasia or adamantinoma. Biopsy showed fibrous stroma consisting of myxofibrous tissue and woven bone which was confirmatory of fibrous dysplasia. Keeping in mind that it was a dormant benign lesion not hindering with functionality of the limb, it was decided to keep the patient under observation with regular follow-up.